Rendition to torture - Clarke, Alan W. (Alan William) (Genocide, political violence, human rights series., 2012)
Many Americans were surprised following the attacks of 9/11 at how easily the United States embraced torture as well as the supposedly lesser evil of cruel, inhuman, and degrading treatment. Extraordinary rendition-sending people captured in the "war on terror" to nations long counted among the world's worst human rights violators-hid from the public eye cruel and bloody interrogations. In Rendition to Torture, Alan W. Clarke explains how the United States adopted torture as a matter of offici.